A Roman Bronze Figurine of a Seated Infant from Shivta in the Negev - Erlich, Adi (Palestine exploration quarterly, 2025)
A small Roman bronze figurine of a seated infant was found in Byzantine Shivta in the arid region of the Negev in southern Israel. The figurine was probably part of a sculptural group or part of a vessel or other utensil. This paper studies the iconography of the figurine, and aims to decipher the gap in time between its production in the Roman period and its discovery in a Byzantine context, some two centuries later. We argue that the Roman figurine was readopted in Byzantine Shivta as an amuletic object, and we strive to explain its function as a miniature relic transferred in time, and perhaps also in place.